Theoretical and applied aspects of of forming of value chain of gas transportation services in system of support of its competitiveness - Запухляк, І. Б. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
In the article a complex scientific ground is carried out teoretiko-applied principles of forming of chain of value of gas-transport services in the system of providing of their competitiveness on internal and world markets. Essence and role of gas-transport enterprises is considered in forming of of a particular branch chain of creation of value. Grounded necessity of integration of the domestic gastransport system for the global chain of value and development of sourcing, outsourcing, offshoring.